Struktur Modal di Tengah Kebijakan Bunga Rendah: Meta-Analisis Jurnal Terakreditasi Indonesia (2019–2024) - Chandra Prasetya Wahyudi; Dea Eka Wulandari; Mufidatul Aini; Much Syahrul Rohmadhon; Nur Zulfatul Laila (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study provides a comprehensive synthesis of ten SINTA-accredited journal articles (levels 1–3) published from 2019 to 2024, examining how a low-interest-rate policy environment affects corporate capital structure in Indonesia. We focus on internal determinants (profitability, firm size, asset composition) versus external factors (market interest rates) in shaping firms’ debt ratios. The meta-analysis results indicate that although low interest rates statistically encourage higher leverage (average coefficient +0.28), internal firm characteristics remain the dominant drivers of capital structure decisions. Approximately 80% of studies report that more profitable firms tend to reduce debt ratios, consistent with the pecking order theory. In the post-pandemic context, low rates initially facilitated cheap borrowing, but heightened economic uncertainty underscores the need for managers to align funding strategy with each firm’s risk profile. The study draws practical implications: financial managers should calibrate capital structure in line with profitability and market volatility, while regulators should monitor corporate debt growth to safeguard financial stability. The findings also suggest directions for future research on how evolving macroeconomic conditions influence corporate finance in Indonesia.